Overcoming of Radioresistance in Non-small Cell Lung Cancer by microRNA-320a Through HIF1α-Suppression Mediated Methylation of PTEN - Xu, Li-Ming; Yu, Hao; Yuan, Ya-Jing; Zhang, Jiao; Ma, Yue; Cao, Xu-Chen; Wang, Jun; Zhao, Lu-Jun; Wang, Ping (Frontiers in Cell and Developmental Biology, 2020)
Background: Radioresistance is a major challenge in the use of radiotherapy for the treatment of lung cancer while microRNAs (miRs) have been reported to participate in multiple essential cellular processes including radiosensitization. This study was conducted with the main objective of investigating the potential role of miR-320a in radioresistance of non-small cell lung cancer (NSCLC) via the possible mechanism related to HIF1α, KDM5B, and PTEN. Methods: Firstly, NSCLC radiosensitivity-related microarray dataset GSE112374 was obtained. Then, the expression of miR-320a, HIF1α, KDM5B, and PTEN was detected in the collected clinical NSCLC samples, followed by Pearson’s correlation analysis. Subsequently, ChIP assay was conducted to determine the content of the PTEN promoter fragment enriched by the IgG antibody and H3K4me3 antibody. Finally, a series of in vitro and in vivo assays were performed in order to evaluate the effects of miR-320a on radioresistance of NSCLC with the involvement of HIF1α, KDM5B, and PTEN. Results: The microarray dataset GSE112374 presented with a high expression of miR-320a in NSCLC radiosensitivity samples, which was further confirmed in our clinical samples with the use of reverse transcription-quantitative polymerase chain reaction. Moreover, miR-320a negatively targeted HIF1α, inhibiting radioresistance of NSCLC. Interestingly, miR-320a suppressed the expression of KDM5B, and KDM5B was found to enhance the radioresistance of NSCLC through the downregulation of PTEN expression. The inhibition of miR-320a in radioresistance of NSCLC was also reproduced by in vivo assay. Conclusions: Taken together, our findings were suggestive of the inhibitory effect of miR-320a on radioresistance of NSCLC through HIF1α-suppression mediated methylation of PTEN.